Retraction: Population genetic structure analysis of Sclerotina sclerotiorum (Lib.) de Bary from different host plant species in northern Iran. Hossein B, Seyed AD, Seyed AR. Arch Biol Sci. 2013;65(1)171-81. DOI:10.2298/ABS1301171B. - Editorial, Journal (Archives of Biological Sciences, 2016)
The article: Population genetic structure analysis of Sclerotina sclerotiorum (Lib.) de Bary from different host plant species in northern Iran. Hossein B, Seyed AD, Seyed AR. Arch Biol Sci. 2013;65(1) 171-81. DOI:10.2298/ABS1301171B, repeats data already published in: Genetic and morphological diversities in Sclerotinia sclerotiorum isolates in northern parts of Iran. Barari H, Alavi V, Badalyan SM. World App Sci J. 2010;8(3)326-33, and published in: Study of genetic variations based on the morphological characteristics, within the population of Sclerotinia sclerotiorum from the major oilseed planting areas in Iran. Barari H, Alavi V. Int J Biol. 2011;3(2)61-6, without any referencing. <a style="color: #ffffff; text-decoration: none; font-weight: bold; margin-left: 1em;" href="https://pubpeer.com/publications/2D2F7A55019A19239DFE0780B9A217?utm_source=Chrome&utm_medium=ChromeExtension&utm_campaign=Extensions">1 comment on PubPeer Link to the retracted article: 10.2298/ABS1301171B <a style="color: #ffffff; text-decoration: none; font-weight: bold; margin-left: 1em;" href="https://pubpeer.com/publications/2D2F7A55019A19239DFE0780B9A217?utm_source=Chrome&utm_medium=ChromeExtension&utm_campaign=Extensions">1 comment on PubPeer .